A New Immunosuppressive Molecule Emodin Induces both CD4+FoxP3+ and CD8+CD122+ Regulatory T Cells and Suppresses Murine Allograft Rejection - Qiu, Feifei; Liu, Huazhen; Liang, Chun-Ling; Nie, Golay D.; Dai, Zhenhua (Frontiers in Immunology, 2017)
Due to vigorous alloimmunity, an allograft is usually rejected without any conventional immunosuppressive treatment. However, continuous global immunosuppression may cause severe side effects, including tumors and infections. Mounting evidence has shown that cyclosporine (CsA), a common immunosuppressant used in clinic, impedes allograft tolerance by dampening regulatory T cells (Tregs), although it inhibits allograft rejection at the same time. Therefore, it is necessary to seek an alternative immunosuppressive drug that spares Tregs with high efficiency in suppression but low toxicity. In this study, we investigated the capacity of emodin, an anthraquinone molecule originally extracted from certain natural plants, to prolong transplant survival in a mouse model and explored the cellular and molecular mechanisms underlying its action. We found that emodin significantly extended skin allograft survival and hindered CD3+ T cell infiltration in the allograft, accompanied by an increase in CD4+Foxp3+ and CD8+CD122+ Treg frequencies and numbers but a reduction in effector CD8+CD44highCD62Llow T cells in recipient mice. Emodin also inhibited effector CD8+ T cells proliferation in vivo. However, CD4+CD25+, but not CD8+CD122+, Tregs derived from emodin-treated recipients were more potent in suppression of allograft rejection than those isolated from control recipients, suggesting that emodin also enhances the suppressive function of CD4+CD25+ Tregs. Interestingly, depleting CD25+ Tregs largely reversed skin allograft survival prolonged by emodin while depleting CD122+ Tregs only partially abrogated the same allograft survival. Furthermore, we found that emodin hindered DC maturation and reduced alloantibody production posttransplantation. Finally, we demonstrated that emodin inhibited in vitro proliferation of T cells and blocked their mTOR signaling as well. Therefore, emodin may be a novel mTOR inhibitor that suppresses alloimmunity by inducing both CD4+FoxP3+ and CD8+CD122+ Tregs, suppressing alloantibody production, and hindering DC maturation. Thus, emodin is a newly emerging immunosuppressant and could be utilized in clinical transplantation in the future.